Unlocking ferroptosis to overcome cancer stem cells-mediated treatment failure and immune evasion - Jin, Weicheng; Xia, Jun; Zhang, Chuanqiang; Shi, Tongguo; Shen, Yu (Frontiers in Immunology, 2026)
Cancer stem cells (CSCs), a small subset of tumor cells with stem cell - like properties, are central to driving tumorigenesis and metastasis. Growing evidence highlights the importance of ferroptosis in maintaining CSCs, positioning ferroptosis as a promising therapeutic strategy. This review explores the interplay between ferroptosis and CSCs, which drive tumor initiation, therapy resistance, and recurrence. It summarizes the mechanisms of ferroptosis involving iron metabolism, lipid peroxidation, and antioxidant defense. The article highlights how non-coding RNAs, metabolic reprogramming, redox homeostasis, and key signaling pathways interconnect ferroptosis with CSC stemness. Furthermore, it discusses the role of ferroptosis in modulating the tumor immune microenvironment and CSC-mediated immune evasion. The identification of stemness and ferroptosis-related biomarkers offers prognostic value, while pharmacological strategies-including traditional Chinese medicine and natural compounds-show promise in targeting CSCs by inducing ferroptosis. Ultimately, leveraging ferroptosis represents a novel therapeutic approach to eliminate therapy-resistant CSCs and improve cancer treatment outcomes.